Community Assistance for KWT Marsudi Luhur in Building a Sustainable Brand Ecosystem for Liquid Organic Fertilizer Products through Digital Branding Optimization - Barida Rakhma Nuranti; Zuchdiawati Luthfi Utami; Reska Anggara Putra; Viant Anggi Saputra (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
This Community Service (PKM) activity aims to empower the Marsudi Luhur Women Farmers Group (KWT) through mentoring in building a sustainable brand ecosystem for Liquid Organic Fertilizer (POC) products. The main problems faced by partners are limited understanding of branding strategies and weak product identity. The method used involves comprehensive mentoring through branding training, product identity development, and digital marketing strategies. The program's effectiveness was evaluated through a pretest-posttest with a validated instrument (item-total correlation of 0.518-0.914) and reliability (α=0.827). The results of the paired sample t-test showed a significant increase in participant knowledge with a p-value <0.001 and an increase in the average score from 35 to 87. The program successfully built the foundation of a sustainable brand ecosystem by increasing branding capacity and strengthening product identity. These findings reflect the importance of an integrated approach a combination of conceptual strengthening, practical development, and technology utilization in empowering community-based MSMEs to compete sustainably.